2014
DOI: 10.3109/01443615.2014.902043
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of intraoperative consultation (frozen section) in borderline ovarian tumours and factors associated with misdiagnosis

Abstract: The objective of our study was to evaluate the accuracy of frozen section (FS) in borderline ovarian tumours (BOT) and to define the factors associated with misdiagnosis during FS evaluation. We performed a retrospective review of patients who underwent exploratory laparotomy for an adnexal mass, from January 2007 to July 2012, at a tertiary oncology centre in Turkey. Patients with a diagnosis of BOT either in FS or in permanent pathology were identified. Agreement between FS diagnosis and permanent histology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Our study demonstrated that the presence of bilateral mBOTs diagnosed by FS had a high probability of being malignant by permanent pathology. This finding is supported by another similar study by Basaran et al., 24 who evaluated patients with a diagnosis of BOT either by FS or permanent pathology and reported that the presence of bilateral tumors was associated with underdiagnosis. Notably, the patients included in the latter study were different from those in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Our study demonstrated that the presence of bilateral mBOTs diagnosed by FS had a high probability of being malignant by permanent pathology. This finding is supported by another similar study by Basaran et al., 24 who evaluated patients with a diagnosis of BOT either by FS or permanent pathology and reported that the presence of bilateral tumors was associated with underdiagnosis. Notably, the patients included in the latter study were different from those in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Of these, 126 evaluated the use of frozen section technique in ovarian neoplasms (Figure 1). Twenty‐one studies discussed the use of qualifying terms in the case of frozen section results that could not rule out invasive carcinoma 6,11‐30 . Eleven of these actually reported on numbers of women with such frozen section diagnoses, using “at least borderline” 11,12,14,16,22,23,25‐28,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies discussed the use of qualifying terms in the case of frozen section results that could not rule out invasive carcinoma. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Eleven of these actually reported on numbers of women with such frozen section diagnoses, using "at least borderline". 11,12,14,16,22,23,[25][26][27][28]30 The study by Robinson et al was excluded from quantitative analysis because it was unclear whether the qualifying terms used in 11 women indicated a suspicion of a borderline ovarian tumor or invasive carcinoma (eg "suggestive of").…”
Section: Evidence Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, accuracy of frozen sections in differentiating SBOTs ranges between 48% and 79%. 37 Several studies have investigated the reason for low accuracy in frozen-section diagnosis of SBOTs and found several clinicopathologic features for prediction of misdiagnosis. 5,38 They reported several factors including histologic type, spread outside the ovary, bilateral disease, and tumor sizes that were significantly associated with misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%